2019
DOI: 10.3389/fonc.2019.00939
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABL Independent Mechanisms of Resistance in Chronic Myeloid Leukemia

Abstract: Not all chronic myeloid leukemia (CML) patients are cured with tyrosine kinase inhibitors (TKIs), and a proportion of them develop resistance. Recently, continuous BCR-ABL gene expression has been found in resistant cells with undetectable BCR-ABL protein expression, indicating that resistance may occur through kinase independent mechanisms, mainly due to the persistence of leukemia stem cells (LSCs). LSCs reside in the bone marrow niche in a quiescent state, and are characterized by a high heterogeneity in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 77 publications
2
86
0
Order By: Relevance
“…Accordingly, we quickly achieved a molecular response with no signs of acute GVHD other than a manageable cutaneous dyskeratosis, and the patients received 5 consecutive DLI injections, continuing to maintain a complete molecular response. Interestingly, the treatment combination produced several immune changes within the BM, that are in line with the reported immunomodulatory activity of this class of drugs (18,19). We indeed observed a "normalization" in bone marrow composition (including a repopulation in precursor and naïve b and T cells) coupled with an unbalance in the CD8/CD4 ratio in favor of the cytotoxic CD8 T cell population, known to be essential for anticancer response (20).…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, we quickly achieved a molecular response with no signs of acute GVHD other than a manageable cutaneous dyskeratosis, and the patients received 5 consecutive DLI injections, continuing to maintain a complete molecular response. Interestingly, the treatment combination produced several immune changes within the BM, that are in line with the reported immunomodulatory activity of this class of drugs (18,19). We indeed observed a "normalization" in bone marrow composition (including a repopulation in precursor and naïve b and T cells) coupled with an unbalance in the CD8/CD4 ratio in favor of the cytotoxic CD8 T cell population, known to be essential for anticancer response (20).…”
Section: Discussionsupporting
confidence: 85%
“…Mutations in drug-targeted proteins lead to changes in protein conformation and insensitivity to anticancer drugs of tumor cells [160]. It has been reported that tyrosine kinase inhibitors are effective to treat chronic myeloid leukemia (CML) by targeting the BCR-ABL protein in CML cells [161,162]. However, the development of drug resistance in patients during treatment is mainly caused by a mutation in the BCR-ABL protein [163,164].…”
Section: Drug Resistance-associated Mutationsmentioning
confidence: 99%
“…These allow interactions between the LSCs and the cells of the microenvironment, which can promote the development of resistance mechanisms. The persistence of LSCs in the presence of TKIs could be the cause of the molecular minimal residual disease that can promote the long-term development of resistance, making them potentially responsible for the clonal evolution and progression of CML [71].…”
Section: Bcr-abl-independent Resistance Mechanismsmentioning
confidence: 99%